(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2020)
Using developed countries as a sample, this research empirically examines the effect and influence of international assistance (ODA) on sustainable development (GDP). As control factors, we use FDI (foreign direct investment) and society (population). The findings of the panel data show that international assistance and economic development have a U-shaped relationship. International assistance has a detrimental effect on a country’s economy at first, but over time, it leads to a country’s economic growth favourable way. Furthermore, the findings clearly endorse the hypothesis that FDI and POP are more prevalent significant determinants of GDP, implying that GDP is less likely to increase be reliant on ODA. Strengthening the legal system will be critical for these countries, as their over reliance on ODA may have negative consequences for overall development. Importantly, good international assistance administration can guarantee that The Sustainable Development Goals (SDGs) are a collection of eight goals that aim to make the world a better place met.